Evaluación de la resistencia genética a manchas foliares en 17 accesiones de maiz (Zea mays l.) en las localidades de Guaranda y Chillanes - Borja Borja, Libia Teresa (2021)
The cultivation of maize worldwide is one of the main foods as an energy source of calories and contributes decisively to food security and sovereignty. In the Andean Zone the great diversity of Phenotypes of corn, are an important part of the different segments of the Maize Value Chain (MVC). In the high land of Ecuador, the cultivation of maize is the most important component of the main production systems and in the province of Bolivar contributes up to 60% of the income of the Agricultural Production Unit (UPA). Due to the process of genetic erosion, and climate change, the processes of collection, characterization, conservation and uses of corn are very important. This research was carried out in the locations of Laguacoto III and in Chillanes, belonging to the Guaranda and Chillanes cantons of Bolivar province. The objectives were: i) To evaluate the main agronomic components of 17 maize collections in two localities. ii) To determine the severity of leaf spots in the maize crop and iii) To select the best collections of soft and hard maize for each agroecological zone according to their agronomic attributes and market demand. The mathematical model of random Complete Block Design was applied with 17 corn Accessions, three repetitions and two locations. The main agronomic components of yield in the vegetative, reproductive and postharvest stages were evaluated. Simple analyses of variance were performed by locality and for the combined performance by two localities, Tukey's test at 5% to compare the mean treatments, main effect for localities, correlation and linear regression. According to the results, there was great variability of treatments within and between the localities, which confirms the strong environmental genotype interaction. The greatest variability of the results occurred between the localities, tolerance to the complex of the leaf spots and the rot of the cob. The Chazo maize Phenotype in Laguacoto III and the improved varieties in the two localities showed a better agronomic adaptation to the climate and soil and due to their tolerance to foliar diseases and being moderately early they escaped the periods of drought stress in Laguacoto and Chillanes to the greater severity of diseases. Within the evaluated germplasm, a great variability was determined in the crop cycle, type of grain (soft, semi-hard and hard), color (white, yellow and black) and the components plant height and insertion of the cob, percentage of plants with cob, length and diameter of the cob and grain yield. Three main groups of maize were defined: soft, semi-hard and hard. Finally, this study allowed to select improved varieties and native Phenotypes for each agroecological zone according to the different segments of the Corn Value Chain.